2013
DOI: 10.1523/jneurosci.4968-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine Signaling in Microglia Contributes to Ectopic Orofacial Pain following Trapezius Muscle Inflammation

Abstract: Fractalkine (FKN) signaling is involved in mechanical allodynia in the facial skin following trapezius muscle inflammation. Complete Freund's adjuvant (CFA) injection into the trapezius muscle produced mechanical allodynia in the ipsilateral facial skin that was not associated with facial skin inflammation and resulted in FKN but not FKN receptor (CX3CR1) expression, and microglial activation was enhanced in trigeminal spinal subnucleus caudalis (Vc) and upper cervical spinal cord (C1-C2). Intracisterna magna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 40 publications
1
45
0
1
Order By: Relevance
“…To our knowledge, our report is the first to address the significance of CX 3 CL1–CX 3 CR1 signaling in a childhood neurodevelopmental disorder devoid of a clear component of neuroinflammation, and suggests a novel therapeutic approach for RTT by targeting CX 3 CR1 with specific antagonists or genetic downregulation. Various “anti-CX 3 CR1” approaches, such as neutralizing antibodies against CX 3 -CR1, small molecule and peptide inhibitors, and CX 3 CR1 siRNA, have been tested in models of other disorders and could have potential therapeutic utilities for RTT (Kiyomoto et al, 2013; Poupel et al, 2013; Wu et al, 2013; Ridderstad Wollberg et al, 2014). Moreover, RTT is highly relevant to our understanding of autism, a group of high-prevalence developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our report is the first to address the significance of CX 3 CL1–CX 3 CR1 signaling in a childhood neurodevelopmental disorder devoid of a clear component of neuroinflammation, and suggests a novel therapeutic approach for RTT by targeting CX 3 CR1 with specific antagonists or genetic downregulation. Various “anti-CX 3 CR1” approaches, such as neutralizing antibodies against CX 3 -CR1, small molecule and peptide inhibitors, and CX 3 CR1 siRNA, have been tested in models of other disorders and could have potential therapeutic utilities for RTT (Kiyomoto et al, 2013; Poupel et al, 2013; Wu et al, 2013; Ridderstad Wollberg et al, 2014). Moreover, RTT is highly relevant to our understanding of autism, a group of high-prevalence developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems likely that persistent hyperexcitability in the pain pathways after disc herniation is associated with a local inflammatory process including activation of macrophages close to the nerve roots. Moreover, previous data show that IL-1 β [24, 25], Csf1 [2628], and CX3CL1 [22, 29, 30] can induce M1 microglia activation. For the first time, however, we showed that application of NP onto the dorsal nerve roots also increased the gene expression of CX3CL1 and CX3CR1 in the NP cells and in the ipsilateral DRGs.…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglial cells change their morphological features, e.g., shrinking of processes or soma swelling (23). Activated microglial cells express phosphorylated p38 and release various molecules (such as brain-derived neurotrophic factor [BDNF]) and cytokines after inflammation and tumor necrosis factor, cytokines, BDNF, ATP, prostaglandin, and nitric oxide after trigeminal nerve injury (24)(25)(26). These molecules bind their receptors, and the excitability of Vc and C1-C2 neurons is modulated.…”
Section: Microglial Mechanisms Underlying Persistent Orofacial Painmentioning
confidence: 99%